2010
DOI: 10.1042/bj20100415
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin-activated human platelets acutely generate oxidized docosahexaenoic-acid-containing phospholipids via 12-lipoxygenase

Abstract: Arachidonate-containing oxidized phospholipids are acutely generated by 12-LOX (12-lipoxygenase) in agonist-activated platelets. In the present study, formation of structurally related lipids by oxidation of DHA (docosahexaenoic acid)-containing phospholipids is demonstrated using lipidomic approaches. Precursor scanning reverse-phase LC (liquid chromatography)-MS/MS (tandem MS) identified a new family of lipids that comprise phospholipid-esterified HDOHE (hydroxydocosahexaenoic acid). Two diacyl and two plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
61
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 24 publications
5
61
0
Order By: Relevance
“…This is similar to previous observations for 12-LOX-derived esterified lipids generated by human platelets. 9,29 In addition, a previous report showed that, although 15-HETE is avidly esterified into neutrophil PLs, little 5-HETE is incorporated. 13 However, we note that these results were obtained with in vitro approaches, and in the future, if it becomes possible to determine the fate of endogenous 5-HETE in vivo, different results may be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to previous observations for 12-LOX-derived esterified lipids generated by human platelets. 9,29 In addition, a previous report showed that, although 15-HETE is avidly esterified into neutrophil PLs, little 5-HETE is incorporated. 13 However, we note that these results were obtained with in vitro approaches, and in the future, if it becomes possible to determine the fate of endogenous 5-HETE in vivo, different results may be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…In platelets, 12-HETE or 14-HDOHE attached to PE or PC are found, whereas EET-PLs in liver predominate as positional isomers reflecting cytochrome P-450 activities (5,12,13). More recently, eoxPLs generated by COX-1 have been found in human platelets.…”
mentioning
confidence: 94%
“…To characterize the molecular species of complex lipids, precursor scanning LC-MS/MS was used, thus "fishing" for molecular ions that incorporated a HETE functional group. Between 2007 and 2012, several families of eoxPLs generated by LOXs were uncovered using this approach, not only in monocytes but also in human platelets, neutrophils, and airway epithelial cells (9)(10)(11)(12)(13)(14). The most abundant were phosphatidylethanolamines (PEs) but PC-derived forms were detected with many being plasmalogens.…”
mentioning
confidence: 99%
“…Although AA is widely studied in platelets, 12-LOX may oxidize a number of other fatty acids on the platelet membrane following stimulation ( 22,44 ). Because thrombin is the most potent activator of platelet function, we investigated the ability of these metabolites to modulate platelet activation following stimulation of the thrombin receptor proteaseactivated receptor-1 (PAR1).…”
Section: Human Platelet Aggregation Dependence Of Fatty Acid Metabolitesmentioning
confidence: 99%